Impact of polyethylene glycol loxenatide on cardiovascular outcomes in patients with type 2 diabetes: study protocol for a multicentre, randomised, double-blind, placebo-controlled trial (BALANCE-3) - Linong Ji; Jian Kuang; Yuanyuan Kong; Yun Xie; Tianpei Hong; Liming Chen; Quanmin Li; Yale Duan (BMJ Open, 2023)
Introduction Recent cardiovascular outcomes trials have demonstrated that glucagon-like peptide 1 receptor agonist (GLP-1RA) decreases the incidence of major adverse cardiovascular events (MACEs) in individuals with type 2 diabetes mellitus (T2DM). Polyethylene glycol loxenatide (PEG-Loxe) is a once-weekly GLP-1RA obtained by modifying exendin-4. No clinical trials have been designed to assess the impact of PEG-Loxe on cardiovascular (CV) outcomes in individuals with T2DM. This trial aims to test the hypothesis that compared with placebo, PEG-Loxe treatment does not result in an unacceptable increase in CV risk in individuals with T2DM.Methods and analysis This study is a multicentre, randomised, double-blind, placebo-controlled trial. Patients with T2DM who fulfilled the inclusion criteria were randomly divided to receive weekly administration of either PEG-Loxe 0.2 mg or placebo (1:1 ratio). The randomisation was stratified according to utilisation of sodium-glucose cotransporter 2 inhibitors, history of CV disease and body mass index. The research period is expected to be 3 years, with a 1-year recruitment period and a 2-year follow-up period. The primary outcome is the occurrence of the first MACE, described as CV death, non-fatal myocardial infarction or non-fatal stroke. The statistical analyses were undertaken on the intent-to-treat patient. The primary outcome was evaluated using a Cox proportional hazards model with treatment and randomisation strata as the covariates.Ethics and dissemination The current research has been authorised by the Ethics Committee of Tianjin Medical University Chu Hsien-I Memorial Hospital (approval number: ZXYJNYYhMEC2022-2). Researchers must acquire informed consent from every participant before conducting any protocol-associated procedures. The findings of this study will be published in a peer-reviewed journal.Trial registration number ChiCTR2200056410.